ANALISIS SISTEM PENGENDALIAN INTERN PENERIMAAN DAN PENGELUARAN KAS PADA CV. BOOM MOTORIST - Hardianti, Gita; Suhardi, Suhardi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
The system in internal control has a very important meaning fot the company, in implements effective internal control so that company goals are achieved. The purpose was to determine the effectiveness of cash receipts and disbursements using yhe internal control system on CV. Boom Motorist. The research approach uses a descriptive method  witha qualitative approach. The sources used are primary obtained from sources and secondary obtained from supporting data. Data collection techiques using direct field observation interviews, observation, and literature study. The results show that the existing system in the company, namely internal control of cash receipts and disbursements, has been effective, but in practice there are functions that have not been separated so that they are still concurrently with one function. Keywords : Internal control System, Cash receipts, Cash disbursements